The cognitive electrophysiology of mind and brain - Zani, Alberto, 1955-; Proverbio, Alice Mado (Academic Press, 2003)
Cognitive electrophysiology is a very well established field utilizing new technologies such as bioelectric events-related potentials (ERP) and magnetic (ERF) recordings to pursue the investigation of mind and brain. Current research focuses on reviewing ERP/ERF findings in the areas of attention, language, memory, visual and auditory perceptual processing, emotions, development, and neuropsychological clinical damages. The goal of such research is basically to provide correlations between the structures of the brain and their complex cognitive functions. This book reviews the latest findings in the areas of attention, language, memory, visual and auditory perception, and brain damage research based primarily on research conducted using ERP recordings. Beyond just compiling the knowledge gained from ongoing research, the authors also identify outstanding problems in the field and predict future developments. Key Features * Provides an original post-cognitive theoretical approach to the investigation of the human mind and brain * Presents integrated view of the emotional and cognitive features as well as of developmental features of neurocognitive systems * Well-illustrated with elegant and original artwork that clarifies complex theoretical and methodological points throughout the text.